Usability Evaluation of the Railfood Feature in the Access by KAI Application Using System Usability Scale Method and Factor Analysis - Farah Aulia Nisa; Ahsanun Naseh Khudori; Wahyu Teja Kusuma (International Journal Software Engineering and Computer Science (IJSECS), 2025)
This study assesses the Railfood feature in the Access by KAI application through System Usability Scale (SUS) methodology and factor analysis. Railfood allows train passengers to order meals online during travel, representing PT Kereta Api Indonesia's move toward digital service integration. Quantitative data from 400 users who accessed the feature within three years revealed a SUS score of 73.5 (Grade C), indicating moderate performance. Satisfaction ranked highest among measured factors, suggesting users found the interface approachable, while efficiency scored lowest due to the initial learning requirements. The gap between these factors points to specific improvement areas: simplifying navigation paths, adding visual cues, and implementing brief tutorials. Such adjustments would likely reduce user adaptation time while maintaining the satisfaction already achieved. The research offers practical value for mobile service development in transportation settings where users operate under time constraints and varying connectivity conditions. Results demonstrate how targeted usability evaluation can identify actionable refinements in transit-based digital services.